Implementasi metode forecasting dalam pengendalian bahan baku jagung dan gandum pada PT ABC - Prasetiawan, Mahendra Putra; Winursito, Yekti Condro (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Efforts to determine optimal raw material control management need to be done to meet production needs This study aims to determine how to forecast demand for Corn and Wheat raw materials at PT ABC. There are two Forecasting methods in the study, namely Moving Average using 2 months and 3 months and Exponential Smoothing with = 0.2 and 0.4 Then to find the most accurate method, the accuracy measurement of the MAD MSE and MAPE forecast results is used. Based on the results of data processing, the measurement error of the forecast results on corn and wheat raw materials was obtained. The results of the Forecasting of Corn raw material demand for the 13th period using the 2 Monthly Moving Average method are 829,442 While the results of the Forecasting of Wheat raw material demand for the 13th period using the Exponential Smoothing method a 0.4 are 125:266. Thus, both methods are expected to be able to increase the efficiency and effectiveness of inventory management in controlling raw materials so as not to experience losses or minimize loss costs.